AIRDOS — open-source PIN diode airborne dosimeter. (25th March 2021) - Kákona, M.; Šlegl, J.; Kyselová, D.; Sommer, M.; Kákona, J.; Lužová, M.; Štěpán, V.; Ploc, O.; Kodaira, S.; Chroust, J.; John, D.; Ambrožová, I.; et al.
Abstract: This article introduces a new open-source dosimeter AIRDOS intended for measurements on board aircraft. In-flight measurement of a mixed radiation field is a challenging deal that requires a small low-power-consumption battery-operated lightweight device with long endurance. A new innovative electronic design with a silicon PIN diode used as a sensor is presented, including full description and manufacturing documentation. The device was verified by measurements and compared with reference dosimeters widely used in aircraft dosimetry, such as Liulin MDU and HAWK TEPC. A comparison of the measurements with a computation model CARI 7 was performed as well. All the comparisons yield positive results within known errors. The new design of the dosimeter has a very satisfactory performance in terms of battery life and does not need calibration after manufacturing or recalibration after a long time of usage. Open-source design predetermines AIRDOS for future improvements and open-science.